Analysis of the State of Research on the Effectiveness of the Philosophical Inquiry Method - Walczak, Paweł (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The aim of the article is to present and analyze the state of research on the effectiveness of the method of philosophical inquiry with children. The method was developed by the American philosopher Matthew Lipman (1923–2010) in the 1970s and, over the last few decades, has found many supporters and enthusiasts around the world. The dynamic development of the method was related to the implementation of numerous evaluation projects of the Philosophy for children (P4C) program, the aim of which was to examine the effectiveness of this method in the context of the development of cognitive and social competences of students. The article analyzes reports and reviews of the most important research projects related to the P4C method, selected on the basis of the adopted methodology, scope, and subject of the research. The conducted analysis leads to the conclusion that the researches on the effectiveness of P4C done so far, confirming that there exists a relationship between the participation of students in classes conducted with the method of philosophical inquiry and the improvement of educational achievements of these students in the area of cognitive and social competence. As a result of the analysis, it was also found that the previous researches did not include the evaluation of the P4C method in the context of improving the competences of teachers working with this method. The potential positive importance of P4C for the development of teachers’ communication and teaching skills is signalled by many theorists and practitioners dealing with philosophizing with children.